USING GEOGEBRA ENVIRONMENT TO VISUALIZE EDUCATIONAL MATERIAL IN THE PROCESS OF TRAINING PRE-SERVICE MATHEMATICS TEACHERS - Dubovyk , Vitalii; Rudnytskyi, Serhii (Physical and Mathematical Education, 2022)
Formulation of the problem. The training of pre-service mathematics teachers requires a high level of visualization of educational material. Integrating a dynamic learning environment GeoGebra can help improve students' skills and knowledge, as well as improve the level of teaching to achieve desired learning goals.Materials and methods The following methods were used in the course of work: theoretical (analysis of scientific and methodological literature to study the state of the problem of using visualization tools by computer mathematics); empirical (observation and systematization of GeoGebra tools in lectures and practical classes of the disciplines "Linear Algebra" and "Differential Geometry and Topology"). It illustrated how one can build and explore space and plane curves with GeoGebra as well as manipulate matrices.Results. This work studies peculiarity of using custom applets and other GeoGebra activities in the process of teaching differential geometry and linear algebra as a part of the pre-service mathematics teachers’ training curriculum. In particular, it describes the affordances of this tool for studying the space curves and forming matrices operations, and finding inverse matrices skills. The advantages and disadvantages of using the GeoGebra environment in the process of teaching linear algebra and differential geometry are highlighted.Conclusions. In today's world, the introduction of information technology in the educational process is a necessary component of the successful mastering of mathematics. GeoGebra is one of the powerful systems of computer mathematics used for dynamic visualization, problem-solving calculations, data processing, and research. This work uses some of the mathematical disciplines to illustrate the benefits of using GeoGebra in the educational process.
Keywords: information technologies; GeoGebra; dynamic mathematics; visualization; differential geometry; linear algebra